Tokyo Start-Up Ecosystem - Mulas, Victor; Astudillo, Pablo; Riku, Takashi; Wyne, Jamil; Zhang, Xin (World Bank, Washington, DC, 2021)
This report analyzes the start-up ecosystem in Tokyo and the greater surrounding area in Japan in the transition of the innovation model to a hybrid of traditional public sector-university-corporation research and development (R and D) combined with start-up agile innovation. It first introduces the role of a start-up ecosystem in contributing to the development of global cities, and thus to the wider national economy. It then takes a country-level view of Japan’s innovation system, within which the metropolitan region operates, in the transition to the innovation-start-up ecosystem. This description is followed by an analysis of the specifics of the Tokyo start-up ecosystem - which consists of investment, support infrastructure, and skills infrastructure - factors that merit close inspection and deep analytics. And finally, the report ends with conclusions - what can be done better or differently to exploit opportunities within Tokyo - but also wider lessons for other global cities.